Short‐Duration AL‐335, Odalasvir, With or Without Simeprevir, in Patients With HCV GT1 or 3 Infection Without Cirrhosis. Issue 6 (19th November 2018) - Gane, Edward J.; Stedman, Catherine A.; Schwabe, Christian; Vijgen, Leen; Chanda, Sushmita; Kakuda, Thomas N.; Fry, John; Blatt, Lawrence M.; McClure, Matthew W.
Abstract : This open‐label, phase IIa study assessed the safety, pharmacokinetics, and efficacy of direct‐acting antiviral agent (DAA) regimens in patients with chronic hepatitis C virus (HCV) infection. Multiple 6‐12‐week oral regimens of 400‐800 mg once daily (QD) AL‐335 + 50 mg QD/every other day odalasvir ± 75‐150 mg QD simeprevir were evaluated in treatment‐naïve, HCV genotype (GT)1/3‐infected patients without cirrhosis. Safety/pharmacokinetic parameters, HCV‐RNA, and sequencing data were assessed. Treatment regimens for later study cohorts were adjusted based on emerging data. In total, 112 patients were enrolled. Three serious treatment‐emergent adverse events occurred, one of which (a Mobitz type 1 second‐degree atrioventricular block [Wenckebach]) was possibly related to high odalasvir exposure and resulted in premature discontinuation of study drugs. No other clinically significant safety findings were identified. GT1‐infected patients receiving 3‐DAA for 6‐8 weeks achieved 100% sustained virologic response 12 weeks and 24 weeks after the end of treatment (sustained virologic response [SVR12/24]). GT1‐infected patients receiving 2‐DAA or GT3‐infected patients receiving 3‐DAA had SVR12/24 less than 90%, whether treated for 8 weeks or 12 weeks. Virologic failure was associated with the emergence of generally persistent NS5A and/or transient NS5B resistance‐associated substitutions in most patients. Pharmacokinetic characteristics of the three drugs were also elucidated. Conclusions: In treatment‐naïve subjects without cirrhosis, AL‐335 + odalasvir + simeprevir for 6‐8 weeks was generally safe and highly efficacious against HCV GT1. However, inadequate efficacy was observed for the 2‐DAA regimen in GT1‐infected subjects and the 3‐DAA regimen in GT3‐infected subjects.